The European CRT Survey: 1 year (9-15 months) follow-up results - Bogale, Nigussie; Gitt, Anselm Kai (European journal of heart failure, 2012)
Aims The European CRT Survey is a joint initiative of the Heart Failure Association (HFA) and the European Heart Rhythm Association (EHRA) of the European Society of Cardiology evaluating the contemporary implantation practice of cardiac resynchronization therapy (CRT) in Europe. Methods and results Patients who had a successful CRT implantation were enrolled from 141 centres in 13 countries between November 2008 and June 2009. Baseline demographics, clinical and implantation data were collected, with a follow-up of ∼1 year (9-15 months). The current report describes clinical outcomes including symptom severity, cardiovascular (CV) hospitalization, and survival. A total of 2438 patients were enrolled, and follow-up data were acquired from 2111 patients (87%). The population included important groups of patients poorly represented in randomized controlled trials, including very elderly patients and those with prior device implantation, atrial fibrillation, and/or QRS duration <120 ms. Investigators reported substantial improvement in New York Heart Association (NYHA) functional class at follow-up. Patient self-assessment indicated that 81% of the patients felt improved, 16% reported no change, and 4% reported deterioration. During follow-up, 207 (10%) patients died, 346 (16%) had a CV hospitalization, and 501 (24%) died or had CV hospitalization. Worse NYHA functional class, atrial fibrillation, ischaemic aetiology, and device type (CRT-P, i.e. CRT alone) were associated with poorer survival. Women had a better outcome, as did patients who had a CRT-D (with an implantable cardioverter defibrillator function) device. Conclusions Outcomes including death and hospitalization in this European CRT survey were consistent with results from clinical trials of CRT. At 1 year follow-up, most patients who received a CRT device considered their symptoms improved compared with their pre-implant assessment. Although prospective, this is an observational study of successful CRT implantations, and outcomes in subgroup analyses must be interpreted with appropriate conservatism. Clinical study no: NCT 01185392